Managed Labor Migration in Afghanistan : A Brief Review of the Academic Migration Literature - Nyarko, Yaw; Chartouni, Carole (World Bank, Washington, DC, 2018)
This paper presents key findings on the international experience with migration, focusing on the implications for a developing nation that is a country of origin. The paper identifies several areas of impacts: (1) increases in wages of individual migrants; (2) remittances; (3) impacts on skills and skill formation – those leaving acquire skills to enhance ability to migrate, and those returning often do so with acquired skills and work experience. Additional impacts also arise on the macroeconomy and on growth of the economy through channels like the use of remittances as collateral, and trade identification and facilitation through migrants. The paper explores the different migration regimes along the spectrum of two polar cases of purely managed and purely unmanaged migration, and focuses on two possible aspects of managed migration: (1) migrants’ social networks, which amplify and propagate the initial actions on migration by the managed systems; and (2) skills and certification systems typically associated with managed systems.